If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(5x + 4) = 5x + -32 Reorder the terms: 6x + -1(4 + 5x) = 5x + -32 6x + (4 * -1 + 5x * -1) = 5x + -32 6x + (-4 + -5x) = 5x + -32 Reorder the terms: -4 + 6x + -5x = 5x + -32 Combine like terms: 6x + -5x = 1x -4 + 1x = 5x + -32 Reorder the terms: -4 + 1x = -32 + 5x Solving -4 + 1x = -32 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + 1x + -5x = -32 + 5x + -5x Combine like terms: 1x + -5x = -4x -4 + -4x = -32 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + -4x = -32 + 0 -4 + -4x = -32 Add '4' to each side of the equation. -4 + 4 + -4x = -32 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = -32 + 4 -4x = -32 + 4 Combine like terms: -32 + 4 = -28 -4x = -28 Divide each side by '-4'. x = 7 Simplifying x = 7
| -3t-8+7t=35+9t-2 | | 40.5=49+1.7(55-60) | | 6=7x+69 | | 14y=32 | | 10lnx=e^4 | | 6st-7su+5sv= | | y=11x^2+x+40 | | 3y=-2x+11 | | 2+7x=4x+8 | | ln(10lnx)=4 | | 6a=-18 | | 18p^2-18=77p | | -9+-6y+6y=-9 | | (5x-12)+(3x-2)=180 | | 4p-3q=23 | | j+556=-7 | | 0.21x+252.00=850 | | 6+40=15x-50 | | 4x+70= | | ln(x-1)-ln(x+1)=2 | | 10x+15y=6 | | 0x+15y=6 | | 8d-(2+d)=42 | | 3p+2q=17 | | 8-7+3= | | 34.4*42= | | d-1-15=45 | | -8z-64=72 | | 2(7x+1)=58 | | b-718=115/6 | | 15Y+4=3Y-8 | | b-7-1/8=11-5/6 |